Genetic screening in patients with ovarian dysfunction. Issue 3 (22nd November 2022) - Zeng, Yang; Li, Lin; Li, Qingchun; Hu, Jijun; Zhang, Nana; Wu, Ling; Yan, Zheng; Qu, Ronggui; Dong, Jie; Liu, Ruyi; Choy, Kwong Wai; Wang, Lei; et al.
Abstract: Ovarian dysfunction, including premature ovarian insufficiency and decreased ovarian reserve, affects the ovarian reserve and is one of the leading causes of female infertility. More and more cases of ovarian dysfunction are associated with genetic factors. Here, we identified eight potential variants in five genes ( MSH4, HFM1, SYCE1, FSHR, and C14orf39) from six independent families by exome sequencing. The splice‐site variants in SYCE1 and MSH4 affected canonical splicing isoforms, leading to missing protein domains or premature termination. Our findings expand the mutational spectrum of ovarian dysfunction and provide potential biomarkers for future genetic counseling and for more personalized treatments. Exome sequencing was shown to be a useful tool to better dissect the genetic basis for ovarian dysfunction and yielded a genetic diagnosis in about 5.0% (6/124) of cases in a cohort of 124 patients with ovarian dysfunction. Abstract : We identified eight potential variants in five genes ( MSH4, HFM1, SYCE1, FSHR and C14orf39 ) from six independent families in infertile females characterized by ovarian dysfunction with exome sequencing. The missense variants in FSHR were conserved across species. And the splice‐site variants in MSH4 and SYCE1 affected canonical splicing isoforms, leading to missing protein domains or premature termination.